A case of acute labyrinthitis due to intra-aural tick infestation: a case report - Ankita Shah; Deepak Paudel; Aman Shah (Journal of Medical Case Reports)
Abstract Background Intra-aural tick infestations, though uncommon, pose a serious clinical challenge owing to the risk of acute labyrinthitis—an inflammatory condition of the inner ear. This inflammation can lead to severe complications such as sensorineural hearing loss, vertigo, and facial nerve palsy. Prompt recognition and management are crucial to prevent these adverse outcomes. Case presentation A 21-year-old female patient of Limbu ethnicity from Dharan presented with sudden-onset right-sided otalgia, accompanied by vertigo, emesis, and auditory impairment. Otoscopic examination revealed a tick lodged in the anteroinferior aspect of the external auditory canal, and audiological assessment indicated profound sensorineural hearing loss on the affected side. Treatment involved careful tick removal using suction and forceps, supplemented by pharmacotherapy including antiinflammatory agents, analgesics, systemic steroids, and prophylactic antibiotics. Her symptoms resolved completely within 4 weeks, with postinterventional audiometry confirming restored auditory acuity. Conclusion This case underscores the importance of prompt clinical assessment and treatment in cases of aural tick infestation. The successful use of a multimodal approach highlights the effectiveness of comprehensive management. Further research is warranted to optimize treatment strategies and improve outcomes in similar cases.